UPAYA PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY PADA KOMPETENSI DASAR MENGELOLA BUKU BESAR PERUSAHAAN DAGANG - Niken Hadiningrum; Dwi Rini Raharti (Pendidikan Ekonomi, 2012)
This study aimed to find our the learning management, students activities, and the learning result after joining the cooperative learning method type Two Stay Two Stray in managing the trading companys ledger Lesson. This study involves the X Accounting 2 class of SMK Negeri 1 Surabaya. By using the class action research, the researcher joins, observes, reflects and evaluates the learning process. The study shows the learning management is 3,00 in the first cycle and increase 3,24 in the second cycle. While, the students activities also increased from 2,95 in the first cycle to 3,41 in the second cycle. Moreover, the mastery learning result increased in the first post test the classical comprehensiveness is 70% and in the second post test increased 87,5%.